2017
DOI: 10.1155/2017/1218254
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Prognostic Value of the Expression of LAMP3 in Oral Squamous Cell Carcinoma

Abstract: Recent studies demonstrated high expression of lysosome-associated membrane protein 3 (LAMP3) in a variety of malignancies including esophageal squamous cell carcinoma, gastrointestinal cancer, breast cancer, and cervical cancer and its involvement in several biological activities of tumor cells. However, the expression of LAMP3 and its value in oral squamous cell carcinoma (OSCC) remain unclear. In this study, we examined the expression of LAMP3 in OSCC tissue samples and investigated the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…In breast cancer, the PERK branch of the UPR increases cell migration upon hypoxic induction through ATF4-mediated induction of lysosomal-associated membrane protein 3 (LAMP3), a lysosomal protein that is also relevant to cancer metastasis [ 140 , 141 ]. The metastatic role of LAMP3 was also further confirmed in head and neck squamous cell carcinoma [ 142 ], oral squamous cell carcinoma (OSCC) [ 143 ], and hepatocellular carcinoma (HCC) [ 144 ] and has recently been reported as a direct target of ATF4 [ 145 ]. Prolonged ERS resulted in irreversible EMT in human peritoneal mesothelial cells (HPMCs), accompanied by activation of the Smad2/3 pathway, nuclear translocation of β -catenin, and expression of Snail [ 146 ].…”
Section: Relationship Between Ers and Emtmentioning
confidence: 99%
“…In breast cancer, the PERK branch of the UPR increases cell migration upon hypoxic induction through ATF4-mediated induction of lysosomal-associated membrane protein 3 (LAMP3), a lysosomal protein that is also relevant to cancer metastasis [ 140 , 141 ]. The metastatic role of LAMP3 was also further confirmed in head and neck squamous cell carcinoma [ 142 ], oral squamous cell carcinoma (OSCC) [ 143 ], and hepatocellular carcinoma (HCC) [ 144 ] and has recently been reported as a direct target of ATF4 [ 145 ]. Prolonged ERS resulted in irreversible EMT in human peritoneal mesothelial cells (HPMCs), accompanied by activation of the Smad2/3 pathway, nuclear translocation of β -catenin, and expression of Snail [ 146 ].…”
Section: Relationship Between Ers and Emtmentioning
confidence: 99%
“…117 However, the expression of LAMP-3 in non-DC cells has different clinical results, and many reports have shown that the expression of LAMP-3 in non-DC (including EC) is closely related to poor prognosis. [118][119][120][121] This may be related to the activation of its downstream signaling pathway.…”
Section: Tumor-associated Macrophages (Tams)mentioning
confidence: 99%
“…This marker is associated with induction and promotion of tumor migration and invasion (12,13). A significant relationship was seen between LAMP3 expression and lymph node metastasis (6,7). Consequently, LAMP3 expression may be a predictor of cancer patient survival (6).…”
Section: Introductionmentioning
confidence: 99%
“…Lysosome-associated membrane protein 3 (LAMP3, CD208, DC-LAMP), a member of the LAMP protein family, is considered a molecular marker of mature dendritic cells (MDCs) (6). Increased LAMP3 expression is associated with unfavorable prognosis in many cancers including esophageal squamous cell carcinoma (ESCC) (7), gastrointestinal stromal tumor (GIST) (8), breast cancers (9, 10), cervical cancer (11), and head and neck squamous cell carcinomas (6). This marker is associated with induction and promotion of tumor migration and invasion (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation